Xenogeneic collagen matrix for the treatment of multiple gingival recessions in esthetics areas: a case series with 24-month follow-up (Research, Society and Development, 2021)
Introduction: Multiple gingival recessions (GR) are often associated with high hypersensitivity and esthetics concerns due to exposed roots. The collagen matrix (CM) associated with coronally advanced flap (CAF) may be a suitable treatment for multiple GR in esthetic areas. However, there is a lack of long term follow up investigations. Objective: To evaluate a 24-month follow-up of the CM + CAF treatment for multiple RT1 GRs in esthetics areas. Materials and Methods: Six patients presenting 6 adjacent Cairo’s gingival recessions type 1 (RT1) in the anterior maxilla were treated with CM + CAF, and based on these patients a brief statistical analysis was conduct. The evaluated parameters included gingival recession depth (GRD), gingival recession width (GRW), probing depth (PD), clinical attachment level (CAL), keratinized tissue width (KTW), gingival thickness (GT), and mean root coverage (MRC). Patient-related outcomes measurements (PROMs) were assessed using an oral health impact profile (OHIP-14) questionnaire and visual analogue scale (VAS).  Results: There was significant improvement in GRD, GRW, and CAL measurements at 3 months postoperatively (p